Exclusion of Criminal Liability and Current Issues in Vietnamese Criminal Law - Hieu, Trinh Duc (VNU Journal of Science: Legal Studies; Vol 41 No 1, 2025)
Clarifying the cases of exclusion of criminal liability helps competent judicial agencies clearly define the distinction between crimes, which are subject to criminal liability and acts that are exempt from criminal liability, creating a basis for lawmakers to build relevant regulations in the Penal Code, contributing to the fight against and prevention of crime, respecting and protecting human rights and civil rights, preventing wrongful convictions and legal errors. Therefore, based on the method of analysis, synthesis, and statistics, the article has made an overall assessment of the research situation on cases of exclusion of criminal liability, thereby pointing out issues that require further research in Vietnamese criminal law in the coming period